Review Article: Analysis of The Food Additive Rhodamine B in Foods Circulated in The Public - Nur Ramdhani Kanata; Chairatun Hisyani Putri; Eti Agustiani; Siti Nurain; Ninda Syaharani; B. Novia Rahmadita Sutanti; Ni Luh Eka Sudiawati Putri; Selvir Anandia Intan Maulidya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Food safety is very important, especially when it comes to snacks that kids and adults eat a lot of. Rhodamine B is still often used as a food coloring, even though it has been banned because it can cause serious health problems, like liver damage and a higher risk of cancer from long-term exposure. This review seeks to investigate the occurrence of Rhodamine B in diverse food products available in the community and to evaluate the analytical methodologies employed in prior research. The research methodology employed is a literature review of national articles published between 2020 untill 2025, utilizing a literature search via Google Scholar with keywords pertinent to Rhodamine B and food analysis. Data were analyzed descriptively according to sample type and analytical methods, including color reaction tests, wool thread tests, thin layer chromatography (TLC), and UV-Vis spectrophotometry, along with the outcomes of Rhodamine B identification. The findings indicated that Rhodamine B was still present in various food items, particularly traditional red cakes, school snack crackers, unbranded jam, red velvet cakes, and certain steamed cakes. Layer cakes, jelly-based foods, cilok sauce, and shrimp paste, on the other hand, were said to not have Rhodamine B in them. This finding stresses the need for ongoing food monitoring and the use of good analytical methods.